THE CHANGES IN SEED QUALITY OF SELECTED PEPPER VARIETIES IN THREE YEARS - Zivkovic, Ivana (Journal on Processing and Energy in Agriculture, 2022)
Pepper (Capsicum annuum L.) as a commercial species includes a large number of different varieties and is one of the most popular vegetables around the world. Changes in the quality of the seeds of autochthonous varieties of pepper seeds: Palanačko Čudo, Župska Rana, and Kobra were monitored in three years (2019–2021). It was noticed that the slightest difference in germination was obtained with the cultivar Palnačko Čudo (p>0.05) in three years. The parish wound had the best germination in 2019 (95%) compared to Palnačko Čudo and Kobra (p
Keywords: seed, pepper, germination, yield.